Nanoporous Titanium Enriched with Calcium and Phosphorus Promotes Human Oral Osteoblast Bioactivity - Pierfelice, Tania Vanessa; D’Amico, Emira; Iezzi, Giovanna; Piattelli, Adriano; Di Pietro, Natalia; D’Arcangelo, Camillo; Comuzzi, Luca; Petrini, Morena (International journal of environmental research and public health, 2022)
Implant surfaces are known to influence the osseointegration process; therefore, their modifications represent an important subject of investigation. On this basis, the purpose of this study was to evaluate the response of human oral osteoblasts (hOBs) to three different GR4 titanium discs: Machined, double-etched (Osteopore), and double-etched, surface-enriched with calcium and phosphorus (CaP) (Nanopore). The superficial topography was investigated with scanning electron microscopy (SEM) and the sessile drop technique. To test cellular response and osteoinductive properties, the following points were evaluated: (i) proliferation by MTS assay after 2 and 5 days; (ii) adhesion by multiphoton microscopy at day 2; (iii) the interaction with Ti discs by blue toluidine staining at day 5; (iv) alkaline phosphatase (ALP) activity by ALP assay after 14 days; (v) calcium deposition by alizarin red staining and by cetylpyridinium chloride after 14 days. The SEM analysis showed that Nanopore and Osteopore surfaces were characterized by the same micro-topography. Nanopore and Osteopore discs, compared to Machined, stimulated higher osteoblast proliferation and showed more osteoinductive properties by promoting the ALP activity and calcium deposition. In conclusion, the CaP treatment on DAE surfaces seemed to favor the oral osteoblast response, encouraging their use for in vivo applications.